Withdrawal of immunosuppressants and low-dose steroids in patients with stable IgG4-RD (WInS IgG4-RD): an investigator-initiated, multicentre, open-label, randomised controlled trial - Peng, Linyi; Nie, Yuxue; Zhou, Jiaxin; Wu, Lijun; Chen, Xiaomei; Wang, Fang; Li, Jieqiong; Peng, Yu; Lu, Hui; Zhao, Lidan; Li, Mengtao; Zhao, Yan; et al. (Annals of the rheumatic diseases, 2024)
ObjectivesIgG4-related disease (IgG4-RD) is an immune-mediated, fibroinflammatory disease. Induction treatment with glucocorticoid (GC) is usually effective, but its tendency of relapse makes the strategy for maintenance treatment a challenge. The WInS IgG4-RD (withdraw immunosuppressants (IMs) and steroid in stable IgG4-RD) trial tested whether discontinuation of GC and IM was feasible in stable IgG4-RD.MethodsThe WInS IgG4-RD trial was a multicentre, open-label, randomised controlled trial. Patients with IgG4-RD receiving GC+IM as maintenance treatment with clinically quiescent disease for at least 12 months were randomised (1:1:1) into three groups: group 1: withdraw GC+IM; group 2: withdraw GC but maintain IM; group 3: maintain GC+IM. The primary outcome was the relapse rate of disease within 18 months. The secondary outcomes included the changes of IgG4-RD Responder Index (RI), Physician’s Global Assessment (PGA), serum IgG4 and IgG, as well as adverse events.ResultsOne hundred and forty-six patients were randomised, with 48 patients in group 1, 49 patients in group 2 and group 3, respectively. Within the 18-month follow-up period, disease relapse occurred in 25 out of 48 (52.1%) patients in group 1 vs 7 out of 49 (14.2%) in group 2 and 6 out of 49 (12.2%) in group 3 (p<0.001). The changes in RI and PGA were significantly higher in group 1 than in group 2 (p<0.001) or group 3 (p<0.001).ConclusionsThe maintenance of IMs, with or without low-dose GC, was found to be superior to withdraw GC+IM in preventing relapse for long-time stable IgG4-RD.Trial registration number NCT04124861.